PROCESS SOLUTIONS IN THE INTERACTION MANAGEMENT OF ENERGY SYSTEMS - G. Avetisayn; A. Raуchenko (Вестник университета)
The article presents the main role of process solutions in the interaction management of energy systems. The article attempts practical implementation of the presented process solutions by the example of energy systems. The arguments for replacing the system approach on the process alternatives are presented.